2014
DOI: 10.1016/j.jviromet.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Application of a modified EDTA-mediated exudation technique and guttation fluid analysis for Potato spindle tuber viroid RNA detection in tomato plants (Solanum lycopersicum)

Abstract: Potato spindle tuber viroid (PSTVd) is a small plant pathogenic circular RNA that does not encode proteins, replicates autonomously, and traffics systemically in infected plants. Long-distance transport occurs by way of the phloem; however, one report in the literature describes the presence of viroid RNA in the xylem ring of potato tubers. In this study, a modified method based on an EDTA-mediated phloem exudation technique was applied for detection of PSTVd in the phloem of infected tomato plants. RT-PCR, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Thus, we measured amino acid concentrations in different plant species by EDTA-exudation, a method preventing sieve element sealing and allowing us to get enough volume to measure amino acids. It has been adopted in many studies 16 20 21 22 23 24 25 26 27 and our results indicated that it was reliable in measuring amino acid concentrations with a relatively low variation among biological replicates ( Fig. 2b ).…”
Section: Discussionmentioning
confidence: 75%
“…Thus, we measured amino acid concentrations in different plant species by EDTA-exudation, a method preventing sieve element sealing and allowing us to get enough volume to measure amino acids. It has been adopted in many studies 16 20 21 22 23 24 25 26 27 and our results indicated that it was reliable in measuring amino acid concentrations with a relatively low variation among biological replicates ( Fig. 2b ).…”
Section: Discussionmentioning
confidence: 75%
“…Both methods lead to either highly diluted phloem sap or very low sample amounts. EDTA-facilitated exudation is also prone to contamination and might not represent the real phloem composition 16 . Spontaneous phloem exudation is limited to plant species like cucurbits, lupine or yucca, where cutting off plant parts leads to a spontaneous emission of phloem sap that can be easily collected 13 17 18 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Guttation is a very common natural phenomenon in the plant kingdom. Many plant species reportedly engage in guttation, such as rice, wheat, barley, maize, tomato, potatoes, tobacco [1][2][3][4][5]. Guttation refers to the process of liquid seeping from the tips, edges, and adaxial and abaxial surfaces of the undamaged leaves of plant species in the form of droplets [6].…”
Section: Introductionmentioning
confidence: 99%